A Difference-Education Intervention Equips First-Generation College Students to Thrive in the Face of Stressful College Situations. (October 2015) - Stephens, Nicole M.; Townsend, Sarah S. M.; Hamedani, MarYam G.; Destin, Mesmin; Manzo, Vida
A growing social psychological literature reveals that brief interventions can benefit disadvantaged students. We tested a key component of the theoretical assumption that interventions exert long-term effects because they initiate recursive processes. Focusing on how interventions alter students' responses to specific situations over time, we conducted a follow-up lab study with students who had participated in a difference-education intervention 2 years earlier. In the intervention, students learned how their social-class backgrounds mattered in college. The follow-up study assessed participants' behavioral and hormonal responses to stressful college situations. We found that difference-education participants discussed their backgrounds in a speech more frequently than control participants did, an indication that they retained the understanding of how their backgrounds mattered. Moreover, among first-generation students (i.e., students whose parents did not have 4-year degrees), those in the difference-education condition showed greater physiological thriving (i.e., anabolic-balance reactivity) than those in the control condition, which suggests that they experienced their working-class backgrounds as a strength.